An analysis of the coherence of descriptors in topic modeling. Issue 13 (1st August 2015) - O'Callaghan, Derek; Greene, Derek; Carthy, Joe; Cunningham, Pádraig
Highlights We evaluate the coherence and generality of topic descriptors found by LDA and NMF. Six new and existing corpora were specifically compiled for this evaluation. A new coherence measure using word2vec-modeled term vector similarity is proposed. NMF regularly produces more coherent topics, where term weighting is influential. NMF may be more suitable for topic modeling of niche or non-mainstream corpora.